2007
DOI: 10.1097/01.prs.0000244748.38742.1f
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in the Previously Augmented Breast

Abstract: Breast cancer in a previously augmented breast raises questions regarding cancer detection and staging, surgical and adjuvant treatment options, reconstructive outcomes, management of the contralateral breast, and continued breast cancer surveillance. This article explores the oncologic and reconstructive issues relevant to women desiring cosmetic breast implants and women with breast cancer who have undergone prior cosmetic breast augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Generally, two surgical treatments are available for removing the tumor in previously augmented patients: breast-conserving surgery and mastectomy [4]. According to Singh et al [8], patients who have undergone augmentation mammoplasty are not ideal candidates for breast-conserving surgery owing to its small breast size, and may experience distortion after lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, two surgical treatments are available for removing the tumor in previously augmented patients: breast-conserving surgery and mastectomy [4]. According to Singh et al [8], patients who have undergone augmentation mammoplasty are not ideal candidates for breast-conserving surgery owing to its small breast size, and may experience distortion after lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have undergone breast augmentation commonly have a low body mass index (BMI), lesser lower abdominal and back tissue limits in harvesting autologous tissues [4]. Meanwhile, skin-sparing mastectomy enables immediate implant-based breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the placement of the implant under the pectoralis major allows better visualization and a larger amount of mammary parenchyma to be examined compared to placement of the implant at the subglandular location, regardless of breast size and type of implant [13][14][15] . Therefore, in patients with a strong family history of breast cancer, it is prudent to avoid using the subglandular plane.…”
Section: Discussionmentioning
confidence: 99%
“…As an aside, submuscular implant placement may interfere less with screening mammography than subglandular implants do. 14,24 Current FDA recommendations to detect implant rupture encourage women with silicone breast implants to undergo screening 3 years after implantation and then every 2 years thereafter; no long-term monitoring is suggested for saline implants. 15 Many plastic surgeons evaluate silicone breast implant patients every 1 to 2 years for contracture and rupture.…”
Section: ■ Implant Longevity and Rupturementioning
confidence: 99%
“…Although they do not necessarily impair mastectomy or breast reconstruction, they may result in an increased rate of revision surgery after breast conservation therapy. 24,36 Mammography remains the standard of care for radiologic diagnosis but can be further supported by MRI and ultrasonography if necessary in patients with implants.…”
Section: ■ Breast Cancer and Detectionmentioning
confidence: 99%